The introduction of Pinus contorta in Sweden - Bäcklund, Sofia (2016)
An increasing demand for forest-based products calls for further development and intensification of forest management. The use of non-native tree species in forestry is a common and expanding silvicultural practice worldwide but the effect of non-native trees on native biodiversity and ecosystem functioning is still poorly understood. The general aim of this thesis is to increase our knowledge about what effects large-scale introduction of a non-native tree species have on forest biodiversity over a chronosequence of forest stand ages. The non-native Pinus contorta and the two native tree species Pinus sylvestris and Picea abies were studied over three age classes (15, 30, 85 years old) of managed forests in northern Sweden to compare the stand- and tree structures, the cover and composition of functional groups of ground vegetation, and the species- and functional diversity of epiphytic lichens. Differences in ground vegetation cover were linked to both tree species and different stand and tree characteristics, but the differences were not consistent over the age classes. Stands of P. contorta had higher cover of vascular plants than the native tree species, and the cover increased with increasing stand age. Trees of P. contorta generally were of larger size than native tree species of comparable age, and also had greater branch surface area in young and middle aged stands, indicating more available substrate for epiphytes. However, the species richness of epiphytic lichens in P. contorta stands was comparable to P. sylvestris and the highest species richness was found in Picea abies stands. Although the forests shared many species, the composition progressively diverged with increasing forest age. Presence of dead branches, greater bark crevice depth and canopy cover generally had positive effect on functional trait diversity, and the reproductive strategy and growth form were the most influential traits on differences in functional diversity between tree species at early successional stages. Generally, the ...